Circulating leptin levels in thyroid dysfunction: a systematic review and meta-analysis - Shanshan Liu; Jun Ma; Leyuan Zhang; Yanlong Yang; Ziqi Han; Limin Tian (BMC Endocrine Disorders)
Abstract Purpose Leptin is an important regulator of energy homeostasis, analogous to thyroid hormone (TH). The purpose of this study was to investigate circulating leptin levels in thyroid dysfunction (TD) patients and the role of TH levels. Methods The electronic databases PubMed, Embase, Cochrane Library, and Web of Science were independently searched by two researchers, from inception until February 3, 2024, and updated on February 15, 2025. Pooled standardized mean difference (SMD) with a 95% confidence interval (CI) was calculated by the random effects model. Results Thirty-eight studies reported circulating leptin levels in TD and control with euthyroidism, 4295 subjects were included in total, of which 1277 were hypothyroidism, 540 were hyperthyroidism, and 2478 were control. Compared to euthyroidism, leptin levels were significantly higher in hypothyroidism, and not significantly altered in hyperthyroidism (SMD [95%CI] = 0.71 [0.38, 1.04] and -0.03 [-0.57, 0.51], respectively). The subgroup analysis indicated that, compared to euthyroidism, leptin levels were significantly higher in subjects regardless of overt and subclinical hypothyroidism (SMD [95%CI] = 0.76 [0.25, 1.26] and 0.41 [0.11, 0.70], respectively), and not significantly different in overt hyperthyroidism (SMD [95%CI] = -0.14 [-0.74, 0.45]). Furthermore, when compared to age-, gender-, and body mass index (BMI)-matched euthyroidism, leptin levels were significantly higher in hypothyroidism and had no significant difference in hyperthyroidism (SMD [95%CI] = 0.66 [0.24, 1.07] and -0.43 [-1.13, 0.27], respectively). A total of 16 studies analyzed the correlations between leptin levels and TH levels in TD, 488 were hypothyroidism and 206 were hyperthyroidism. Following correlation analysis, leptin levels displayed a positive correlation with thyroid-stimulating hormone (TSH) levels (r = 0.19) and a negative correlation with triiodothyronine (T3) levels (r = -0.40) in TD. Conclusion Compared to euthyroidism, circulating leptin levels were significantly higher in hypothyroidism, and not significantly altered in hyperthyroidism. Besides, leptin levels in TD may be directly regulated by TSH and T3 levels, independent of BMI. Trial registration CRD42024561055.